Amphiphilic Molecules of Nb18: Synthesis, Langmuir-Blodgett Films Construction and Applications in Electro-Catalysts. Issue 4 (1st January 2015) - Huang, Mei; Mao, Xiaoli; Chen, Dechao; He, Shulian; He, Shuai; Liu, Wenhong; Xu, Jinzhang; Miao, Shiding
Abstract : A new type of Nile blue (Nb) derivative molecules terminated with long-chain alkyl (termed as Nb18) has been synthesized from precursors of barium stearate and 3-amino-7-(diethylamino)-1, 2-benzophenoxazin sulfate. Optical characterizations including UV-Vis absorption, fluorescence emission, excitation spectra and the infrared spectroscopy reveal a blueshift in the band emission of Nb18 as compared to the Nb molecule, and this shift was found to be reasoned by incorporation of long-chain alkyl groups and replacement of SO4 2− . The amphiphilic Nb18 molecules were found to form stable Langmuir monolayers over aqueous solutions, and this allows one to study the kinetics of Nb18 formation by means of surficial chemistry. The synthetic reaction was demonstrated to have first-order kinetics with a rate constant of ∼0.0033 s −1 . Using different techniques (Langmuir-Blodgett and Langmuir-Schaefer) monolayers of Nb18 were deposited on an electrode where the amphiphilic molecules were differently oriented. Investigation of these films undertaken to confirm some of the previous electrochemical observations indicated that the electro-catalytic activity stems from the cationic rings of aromatic oxazine regarding to the oxidation of dihydronicotinamide adenine dinucleotide (NADH).